Use and Complications of Temporary Hemodialysis Catheters at Hemodialysis Unit at Tishreen University Hospital in Lattakia - سليمان, ابراهيم; عباس, عبد الفتاح; رستم, ميخائيل (Latakia University Journal -Medical Sciences Series, 2021)
Background: Temporary Hemodialysis catheters complications are still considered a significant cause of morbidity and mortality of hemodialysis(HD) patients. Aims: Our research aimed to study use and investigate the incidence rates of temporary hemodialysis Catheter complications in HD patients, and to study the risk factors predisposing to these complications. Settings and Design: This was a one year prospective observational study conducted in a hemodialysis unit, department of nephrology, Tishreen university hospital, over the year 2019. Methods and Material: 62 Temporary hemodialysis catheters in 40 HD patients were recruited for the study, the Catheters were inserted under strict asepsis and heparin solution was used to lock the whole catheter-lumen and they were subjected to regular observation in every HD session. Culture and sensitivity of a catheter-tip was performed to confirm the diagnosis of infection after the removal of the catherter due to fever. Results: The majoraty of catheters were electively removed due to the end of the need of treatment with hemodialysis.Catherter dysfuntion was the most leading coplication that lead to the removal of catheters (38,7%), followed by catherter related infection (11,3%). Catheter dysfunction was the most frequent complication (38,7%) and connected to the location of the catheter, the duration of its use, the use of a previous catheter in the same location and the type of renal faliure, followed by fever (27,4%) which connected to the duration of the catheter and the type of renal faliure. Conclusions: Temporary hemodialysis catheter complications are not rare, and they could lead to the removal of the catheter. So, it´s necessary to make more efforts and work as a multidisciplinary team.